2020
DOI: 10.1186/s12909-020-02302-2
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the acceptance of blended learning in medical education: application of UTAUT2 model

Abstract: Background Blended learning is a new approach to improving the quality of medical education. Acceptance of blended learning plays an important role in its effective implementation. Therefore, the purpose of this study was to investigate and determine the factors that might affect students’ intention to use blended learning. Methods In this cross-sectional, correlational study, the sample consisted of 225 Iranian medical sciences stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
67
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 45 publications
21
67
1
2
Order By: Relevance
“…Local reports established that students' acceptance of the use of Google Classroom was positive (Nor Zanira & Hafizul, 2020;Syed Ahmad et al, 2020). The factors of performance expectancy, effort expectancy, social influence, and facilitating conditions influence an individual's intention to employ new technology (Azizi et al, 2020). Furthermore, this study discovered that the facilitating conditions factor recorded the highest mean, followed by effort expectancy, performance expectancy, and social influence, respectively.…”
Section: Discussionmentioning
confidence: 69%
“…Local reports established that students' acceptance of the use of Google Classroom was positive (Nor Zanira & Hafizul, 2020;Syed Ahmad et al, 2020). The factors of performance expectancy, effort expectancy, social influence, and facilitating conditions influence an individual's intention to employ new technology (Azizi et al, 2020). Furthermore, this study discovered that the facilitating conditions factor recorded the highest mean, followed by effort expectancy, performance expectancy, and social influence, respectively.…”
Section: Discussionmentioning
confidence: 69%
“…The extended model with LV could be applied with students of different disciplines, in different countries, in the eLearning and blended learning context. For example, Azizi et al ( 2020 ) reported that almost all UTAUT2 constructs (PE, EE, SI, FC, HM, PV, HT) significantly affected students’ BI to use blended learning. Future research is suggested to investigate students’ intentions and use of specific digital platforms and online environments, as well as Universities’ digital infrastructure.…”
Section: Implications and Future Researchmentioning
confidence: 99%
“…Organizational factors such as facilitation conditions are not of less importance. Whereas, Social factors, such as social influence, significantly affect students' behavioral intention to use blended learning (Azizi, Roozbahani & Khatony, 2020). Successful Blended Learning implementation requires successful implementation and use of eLearning in addition to face-to-face learning.…”
Section: What Blended Learning Needsmentioning
confidence: 99%